LONG-TERM PHOTOMETRIO MONITORING OF CATACLYSMIC VARIABLES: PRELIMINARY RESULTS FOR Т CRB, CQ DRA AND GK PER - Petrik, K.; Hrik, L.; Niarchos, P.; Urban, Z.; Velic, Z. (Одеські астрономічні публікації, 2017)
The preliminary results oГ the longterm photometric monitoring (LTPM) oГ cataclysmic variables (СVs) Т CrB, CQ Dra and GK Per are presented. All the observational data were obtained in the frame oГ the international campaigns oГ the observations oГ cataclysmic and symbiotic stars.